2020
DOI: 10.1001/jamapsychiatry.2020.1011
|View full text |Cite
|
Sign up to set email alerts
|

Coached Mobile App Platform for the Treatment of Depression and Anxiety Among Primary Care Patients

Abstract: IMPORTANCE Depression and anxiety are common and disabling. Primary care is the de facto site for treating these mental health problems but is typically underresourced to meet the burden of these demands.OBJECTIVE To evaluate the efficacy of a mobile intervention platform, IntelliCare, for addressing depression and anxiety among primary care patients.DESIGN, SETTING, AND PARTICIPANTS Two-arm randomized clinical trial at internal medicine clinics at the University of Arkansas for Medical Sciences. Adult primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 46 publications
3
117
1
4
Order By: Relevance
“…We note that the study was underpowered to detect changes in psychosocial targets, so we are unable to determine if the lack of change was because of chance. Compared with previous studies of IntelliCare in which participants were encouraged to use IntelliCare daily, participants in this study were not given this instruction and used IntelliCare less frequently during the 8-week study than had been observed in these previous studies [ 6 - 8 ]. Participants enrolled in this study during the summer months, and the 8-week follow-up for many participants took place after the fall semester began.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We note that the study was underpowered to detect changes in psychosocial targets, so we are unable to determine if the lack of change was because of chance. Compared with previous studies of IntelliCare in which participants were encouraged to use IntelliCare daily, participants in this study were not given this instruction and used IntelliCare less frequently during the 8-week study than had been observed in these previous studies [ 6 - 8 ]. Participants enrolled in this study during the summer months, and the 8-week follow-up for many participants took place after the fall semester began.…”
Section: Discussionmentioning
confidence: 92%
“…The IntelliCare app platform has demonstrated efficacy in reducing symptoms of depression and anxiety in general adult populations [ 6 - 8 ]. IntelliCare is a collection of quick and easy-to-use apps that each present a different evidence-based mood management strategy (eg, cognitive restructuring, behavioral activation).…”
Section: Introductionmentioning
confidence: 99%
“…This is a case study report of 3 participants of the 146 adults enrolled in a randomized controlled trial investigating the efficacy of the IntelliCare intervention among primary care patients with depression and/or anxiety [ 15 ]. The UAMS Institutional Review Board approved this study, and all participants provided informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a clinical trial evaluating IntelliCare, an evidence-based mobile intervention for depression and anxiety, among adults recruited from primary care clinics at the University of Arkansas for Medical Sciences (UAMS) [ 14 , 15 ]. IntelliCare has been publicly available since 2014 and has shown favorable results in 2 previous trials, with past users demonstrating high engagement (>90% continued use through 8 weeks of treatment in coached deployments) and substantial improvements in depression symptoms from pre- to postintervention [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The IntelliCare app platform has demonstrated efficacy in reducing symptoms of depression and anxiety in general adult populations [6][7][8]. IntelliCare is a collection of quick and easy-to-use apps that each present a different evidence-based mood management strategy (eg, cognitive restructuring, behavioral activation).…”
Section: Introductionmentioning
confidence: 99%